The 7 habits of highly effective people : powerful lessons in personal change - Covey, Stephen R. (London : Simon & Schuster, 2013)
When it was first published in 1989, The 7 Habits of Highly Effective People was an almost instant bestseller--and quickly became a permanent part of the cultural lexicon. With over 25 million copies sold worldwide in over 40 languages since its first publication, this book continues to help millions of readers become more effective in both their personal and professional lives. This is one of the rare books that has influenced presidents, CEOs, educators, and individuals all over the world not only to improve their businesses and careers but to live with integrity, service, dignity, and success in all areas of life. It has had an undeniable impact for the past 25 years--and will no doubt continue to be influential for many more. ENDORSEMENTS "Every so often a book comes along that not only alters the lives of readers but leaves an imprint on the culture itself. The 7 Habits is one of those books."--Daniel Pink, author of Drive and To Sell Is Human "The 7 Habits encompass timeless principles that can help guide any company toward success." --Tony Hsieh, New York Times bestselling author of Delivering Happiness and CEO of Zappos.com, Inc. "There are very few business books that are essential reading for anyone who wants to make a difference. This is one of the great ones." --Seth Godin, author of The Icarus Deception "No person lasts forever, but books and ideas can endure. Stephen R. Covey's life is done, but his work is not. It continues, right here in this book as alive today as when first written." --Jim Collins "Twenty-five years after it first appeared, the wisdom of The 7 Habits is more relevant than ever. On an individual level people are burning out, and on a collective level we are burning up the planet. So Dr. Covey's emphasis on self-renewal, and his understanding that leadership and creativity require us to tap into our own physical, mental, and spiritual resources, are exactly what we need now.
Includes index.
Keywords: Success -- Psychological aspects; Character; Efficiency